Design of a New Drip Irrigation Belt Recovery Machine with Anti Breakage Function - Junhui Ran; Zhipeng Song; Quan Zhang; Wensong Guo; Xufeng Wang (Agriculture, 2024)
Drip irrigation technology is widely used in agricultural production in the Xinjiang region. However, there are still a series of problems in the mechanized recovery of field drip irrigation belts, such as easy breakage of drip irrigation belts, low recovery efficiency, and excessive doping of recycled drip irrigation belts. This study focused on the problems of mechanized recovery of drip irrigation belts in Xinjiang and designed a new type of drip irrigation belt recovery machine. The key mechanisms of the new drip irrigation belt recovery machine were designed and theoretically analyzed, and their basic parameters were determined. Then, the superiority of the new drip irrigation belt recovery machine’s operational performance was verified through experiments. The experimental results showed that the new drip irrigation belt recovery machine is superior to existing machines in terms of the drip irrigation belt recovery rate and operational efficiency. In addition, the drip irrigation belts recovered by the newly designed machine have low impurity content. During the recovery process, the new machine requires less labor input than that of the existing machine.